Pemahaman Nilai-Nilai Kepahlawanan Soekarno Dalam Pembentukan Karakter Peserta Didik Melalui Model Pembelajaran Role Playing - Muhammad Gazali Bancin; Corry Corry; Bongguk Haloho (Departement of Mathematics Education, 2023)
This research was conducted with the aim of knowing the understanding of Soekarno's heroic values in shaping the character of students with the Role Playing model. The method used in this research is descriptive-qualitative research method. Qualitative descriptive research is research that aims to describe, summarize various conditions, as situations or various reality phenomena that exist in society which are the object of research and seeks to draw that reality to the surface as a characteristic, character, model, sign or description of the condition, situation or certain phenomenon. The results of the study show that the understanding of Soekarno's heroic values is very influential in the formation of the character of students with the role playing model. Learning history, will develop students' activities to study various events, to then be understood and internalized to themselves so as to give birth to examples for behaving and acting.